Potensi Penggunaan Limbah Kulit Menjadi Aksesoris - Soemolang, Lorenza Michelle; Hairunnas (Meraki: Journal of Creative Industries, 2024)
considering the nature of leather waste which is difficult to decompose and the widespread production of leather products in Indonesia has resulted in a large amount of leather waste not being recycled. This research aims to explore the potential for using leather waste in making accessories, with a focus on developing appropriate methods and processes. The methodology includes qualitative analysis of the characteristics of leather waste and observation of its potential as an accessory material. The main findings include identifying the types of leather waste that are most suitable for making accessories, as well as determining optimal processing techniques. In conclusion, managing leather waste for making accessories has significant potential and can be an important step in efforts to reduce waste and increase the sustainability of the leather industry.